2011
DOI: 10.12659/msm.881762
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pretreatment with H2 receptor antagonists on the cure rates of Helicobacter pylori eradication

Abstract: SummaryBackgroundPretreatment with a proton pump inhibitor (PPI) reportedly decreases the efficacy of Helicobacter pylori (H. pylori) eradication, however, the effect of pretreatment with an H2 receptor antagonist (H2RA) on H. pylori eradication has not yet been studied. We compared the efficacy of eradication regimen (lansoprazole/amoxicillin/clarithromycin) in patients with H. pylori infection with or without H2RA pretreatment.Material/MethodsIn this retrospective study conducted at three centers, 310 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A large number of other studies looked at the role of phytomedicine in H. pylori eradication therapy. In vitro anti-H. pylori activity was observed when the Terminalia macroptera root was used and also for Eucalyptus tolleria leaf extract (when used with clarithromycin) [53,54]. Interestingly, in drug-resistant strains, Combretum molle and Sclerocarya birrea were shown to be potentially effective in vitro [55,56].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…A large number of other studies looked at the role of phytomedicine in H. pylori eradication therapy. In vitro anti-H. pylori activity was observed when the Terminalia macroptera root was used and also for Eucalyptus tolleria leaf extract (when used with clarithromycin) [53,54]. Interestingly, in drug-resistant strains, Combretum molle and Sclerocarya birrea were shown to be potentially effective in vitro [55,56].…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…As H2RA does not influence H. pylori transformation, theoretically, H2RA pretreatment might be more suitable to improve the H. pylori eradication efficacy than PPI. A retrospective study has observed that the H2RA pretreatment group achieved a marginally higher H. pylori eradication rate when compared to the standard triple therapy group (81.6% vs. 77.6%, p = 0.3799) (Tokoro et al 2011), suggesting the possibility of H2RA pretreatment for H. pylori eradication; however, it was limited by the retrospective nature, including heterogeneous H. pylori eradication regimen, various durations (1-150 days) of H2RA pretreatment, and diverse kinds and dosages of H2RA. Thus, the previous retrospective study is insufficient to evaluate the effect of H2RA pretreatment on H. pylori eradication efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was the success rates of H. pylori eradication after completion of the entire regimen. Based on a previous study in a similar setting, the sample size was calculated assuming an 85% eradication rate as the primary endpoint in the pretreatment group and 70% in the control group (Tokoro et al 2011;Kim et al 2015). We estimated that a sample size of 120 patients per group would have a statistical power of 80% and a two-sided α-risk of 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the effect of pretreatment with H2 receptor antagonist (H2RA) is unclear. Only one report suggested that pretreatment with H2RA had no significant influence on the efficacy of H. pylori eradication treatment [13]. The present retro-spective study analyzed whether pretreatment with PPI or H2RA decreases or dose not decrease the probability of H. pylori eradication.…”
Section: Introductionmentioning
confidence: 90%